2022
DOI: 10.1177/15533506221092492
|View full text |Cite
|
Sign up to set email alerts
|

A First Reported Adjustable Breast Volume Simulator for Teaching Oncoplastic Surgery Marking: Adjustable Breast Oncoplastic Surgery Simulator

Abstract: Background The current simulators for teaching oncoplastic surgery marking are available in a fixed size for each model. This is not an accurate reflection of the variety of patient’s breast volumes in reality and may limit the teaching to certain techniques associated with the particular breast ptosis/size. Device description This is the first reported simulator with varying breast volumes/ptosis in a single model for teaching oncoplastic surgery marking, known as Adjustable Breast Oncoplastic Surgery Simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Papavasiliou et al developed a 3D printed chest wall as an adjunct to the current chicken thigh model that mimics the anastomosis performed during DIEP breast reconstruction, representing a simple and cost-effective enhancement that provides a significantly more realistic resemblance to a clinical situation than the original model [ 98 ]. Lastly, Lim et al reported the use of a novel simulator with different breast volumes and ptosis grades in a single model for teaching marking in oncoplastic surgery [ 99 ]. In this regard, the future of plastic surgery education is exciting because of the ability to take a two-dimensional (2D) image and bring it to life with a full-scale model [ 20 , 63 ].…”
Section: Three-dimensional Printing As An Educational Toolmentioning
confidence: 99%
“…Papavasiliou et al developed a 3D printed chest wall as an adjunct to the current chicken thigh model that mimics the anastomosis performed during DIEP breast reconstruction, representing a simple and cost-effective enhancement that provides a significantly more realistic resemblance to a clinical situation than the original model [ 98 ]. Lastly, Lim et al reported the use of a novel simulator with different breast volumes and ptosis grades in a single model for teaching marking in oncoplastic surgery [ 99 ]. In this regard, the future of plastic surgery education is exciting because of the ability to take a two-dimensional (2D) image and bring it to life with a full-scale model [ 20 , 63 ].…”
Section: Three-dimensional Printing As An Educational Toolmentioning
confidence: 99%